Efektivitas Media Google Sites Dalam Pembelajaran Bahasa Indonesia Kelas VII SMP - Meldiani, Cantika (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
This research aims to determine the effectiveness of Google Sites learning media on Indonesian language learning. Describe the attraction of students in learning using Google Sites and describe the relationship between Google Sites and students' interest in studying Indonesian language subjects. The research method used is qualitative with a descriptive approach. The data obtained came from observations in online learning practices using Google Sites and online interviews. Then the data is interpreted with narrative. Based on the research results obtained, Google Sites media is an effective media for class VII middle school students. It is known that effective learning is learning that provides independent and active learning opportunities and carries out various activities according to their needs. This research has shown the effectiveness of learning media for students to be able to learn comfortably, happily and calmly because the material presented can be packaged as attractively and creatively as possible by educators so that students can understand the learning material easily. Apart from that, there are several other benefits from using Google Sites learning media, namely: 1) flexible learning, 2) learning that creates student independence, 3) increasing technological knowledge, 4) expanding learning materials, 5) saving costs, 6) Minimize boredom in learning activities.